Influence of phosphated cross-linked high amylose on in vitro release of different drugs - Cury, Beatriz S. F. [UNESP]; de Castro, Ana Doris [UNESP]; Klein, Stanlei Ivair [UNESP]; Evangelista, Raul Cesar [UNESP] (Elsevier B.V., 2009)
The influence of structural characteristics of high amylose cross-linked at different degrees on the release of drugs with important molecular differences, namely sodium diclophenac (SD) and nicotinamide (NI), was assessed in vitro from non-compacted systems. The release profiles were related with classical kinetic mathematical models for better understanding of the release mechanism. An increase in polymer cross-linking degree resulted in longer release time for both drugs, although SD generally was released slower than NI. SD release from samples cross-linked at 2% of basis was driven mainly by Fickian diffusion, while from samples cross-linked at 4% of basis follows anomalous mechanism. Inversely, anomalous mechanism was responsible for NI release from 2% samples and Fickian diffusion from 4% samples. Results suggest that the performance of cross-linked high amylose as excipient for controlled drug release not only depends on cross-linking degree but also is highly influenced by structural characteristics of the drug. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: High amylose; Cross-linking; Nicotinamide; Sodium diclophenac; Release mechanism